Adherence to Statin Therapy Among US Adults Between 2007 and 2014 - Colantonio, Lisandro D.; Rosenson, Robert S.; Deng, Luqin; Monda, Keri L.; Dai, Yuling; Farkouh, Michael E.; Safford, Monika M.; Philip, Kiran; Mues, Katherine E.; Muntner, Paul (Journal of the American Heart Association, 2019)
Background Prior studies suggest that persistence with and adherence to statin therapy is low. Interventions to improve statin persistence and adherence have been developed over the past decade. Methods and Results This was a retrospective cohort study of adults aged ≥21 y with commercial or government health insurance in the MarketScan (Truven Health Analytics) and Medicare databases who initiated statins in 2007-2014 and (1) started treatment after a myocardial infarction (n=201 573), (2) had diabetes mellitus but without coronary heart disease (CHD; n=610 049), or (3) did not have CHD or diabetes mellitus (n=2 244 868). Persistence with (ie, not discontinuing treatment) and high adherence to statin therapy were assessed using pharmacy fills in the year following treatment initiation. In 2007 and 2014, the proportions of patients persistent with statin therapy were 78.1% and 79.1%, respectively, among those initiating treatment following myocardial infarction; 66.5% and 67.3%, respectively, for those with diabetes mellitus but without CHD; and 64.3% and 63.9%, respectively, for those without CHD or diabetes mellitus. Between 2007 and 2014, high adherence to statin therapy increased from 57.9% to 63.8% among patients initiating treatment following myocardial infarction and from 34.9% to 37.6% among those with diabetes mellitus but without CHD (each P <0.001). Among patients without CHD or diabetes mellitus, high adherence did not improve between 2007 (35.7%) and 2014 (36.8%; P =0.14). In 2014, statin adherence was lower among younger, black, and Hispanic patients versus white patients and those initiating a high-intensity statin dosage. Statin adherence was higher among men and patients with cardiologist care following treatment initiation. Conclusions Persistence with and adherence to statin therapy remain low, particularly among those without CHD.